Analysis of the Use and Acceptance of Government Social Media in the South Sumatra Community Using the UTAUT 2 Method (Case Study : Instagram of the South Sumatra Provincial Food Crop and Horticulture Agriculture Office @pertaniantph.sumsel) - Falah, Miftahul; Wedhasmara, Ari; Putri, Amelia Rizki; Tania, Ken Ditha; Ibrahim, Ali; Sevtiyuni, Putri Eka (Fakultas Ilmu Komputer, Universitas Sriwijaya, 2025)
The widespread accessibility of the internet via smartphones, laptops, and tablets, along with the convenience of carrying these devices anywhere, has transformed social media from merely a communication tool into a key source of information. Instagram, in particular, focuses on visual aesthetics. Many government agencies in Indonesia now have Instagram accounts to engage with the public, as social media-especially Instagram-is increasingly viewed as a popular platform for information dissemination across various demographic groups. One such agency is the South Sumatra Provincial Food Crop and Horticulture Agriculture, which operates under the Instagram handle @pertaniantph.sumsel. However, engagement with their Instagram community remains low, as seen from the limited number of likes and comments on their posts. To investigate the factors contributing to this issue, a study was conducted using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) model, gathering data from 516 questionnaire respondents who follow the @pertaniantph.sumsel account. The data was analyzed using SmartPLS, revealing that Behavioral Intention significantly impacts Usage Behavior, Effort Expectancy significantly affects Behavioral Intention, Facilitating Conditions influence Usage Behavior, Habit has a significant impact on Behavioral Intention, Hedonic Motivation affects Behavioral Intention, and Social Influence also plays a key role in shaping Behavioral Intention.